The Department of Faculty Surgery soon will be celebrating 80 years since its establishment in Kaunas Vytautas Magnus University: historical overview of the Department of Faculty Surgery in Kaunas - Zykas, Vytautas; Venskutonis, Donatas; Vaičys, Žygimantas (Lietuvos chirurgija, 2019)
Department of Faculty Surgery in Kaunas was established in 1940 in Vytautas Magnus University. At that time the Dean of Medical Faculty and temporary chief of Surgery Department professor Vladas Lašas reorganized it by splitting and establishing two surgical departments – so called Faculty and Hospital Surgery. The Department has been renamed several times in subsequent years: until 1982 it continued to be Department of Faculty Surgery, in 1982–1992 was renamed to 2nd Surgery Department, in 1992–1998 carried the name of 2nd Surgery Clinic. This article offers an overview about prominent surgeons, who educated further generation of surgeons and created academic surgery, such as prof. V. Kanauka, prof. V. Lašas, A. Stropus, assoc. prof. J. Jaržemskas, assoc. prof. J. Karaliūnas, assoc. prof. J. Platūkis, prof. V. Zykas, prof. D. Venskutonis, also their collaborators and successors. The overview of academic, scientific progress as well as major contribution in the development of proctology in Lithuania is presented and includes the period until 1998 when Department underwent further reorganization by establishing new Department of General Surgery.